drdof the genotype of HSP70B gene in some characteristics of the components of milk - Ghadeer Razak Ahmed; Abdullah Hamid Salem (University of Thi-Qar Journal of agricultural research, 2022)
The study was conducted at Taj Al-Nahrain station in Al- Diwaniyah Governorate, which Is approximately 200 km from the center of Dhi Qar Governorate, for the period from 10/2/2021 to 1/4/2022.And the laboratory part of the study was conducted In the Molecular Genetics Laboratory of the Marshes Research Center at Dhi Qar University. The study includeincludeed 49 Holstein cows Imported in their third productive season, Blood samples were drawn from them for the purpose of separating the genetic material (DNA) from It and studying the heat shock protein HSPA6 gene and knowing Its relationship to milk production characteristics In Holstein cows ,The results showed the nucleotide sequence on the 475bp gene segment extracted from the HSP70B gene the presence of the point mutation G˃T.113 was detected In the third exon of the above gene In the cattle sample under study. And the mutation discovered In the studied piece of the HSP70B gene was a missense mutation and It worked to change the code for the amino acid valine to private code With the amino acid lucine .Three genotypes were shown: GG, GT, and TT. Groups of cows carrying the genotypes (GG, GT and TT) did not differ significantly among themselves in the characteristics of milk components, but an arithmetic superiority between the three genotypes was noticed and referred to in all the studied traits.